Chemical composition and source of fine and nanoparticles from recent direct injection gasoline passenger cars: Effects of fuel and ambient temperature. (January 2016) - Fushimi, Akihiro; Kondo, Yoshinori; Kobayashi, Shinji; Fujitani, Yuji; Saitoh, Katsumi; Takami, Akinori; Tanabe, Kiyoshi
Abstract: Particle number, mass, and chemical compositions (i.e., elemental carbon (EC), organic carbon (OC), elements, ions, and organic species) of fine particles emitted from four of the recent direct injection spark ignition (DISI) gasoline passenger cars and a port fuel injection (PFI) gasoline passenger car were measured under Japanese official transient mode (JC08 mode). Total carbon (TC = EC + OC) dominated the particulate mass (90% on average). EC dominated the TC for both hot and cold start conditions. The EC/TC ratios were 0.72 for PFI and 0.88–1.0 (average = 0.92) for DISI vehicles. A size-resolved chemical analysis of a DISI car revealed that the major organic components were the C20 –C28 hydrocarbons for both the accumulation-mode particles and nanoparticles. Contribution of engine oil was estimated to be 10–30% for organics and the sum of the measured elements. The remaining major fraction likely originated from gasoline fuel. Therefore, it is suggested that soot (EC) also mainly originated from the gasoline. In experiments using four fuels at three ambient temperatures, the emission factors of particulate mass were consistently higher with regular gasoline than with premium gasoline. This result suggest that the high content of less-volatile compounds in fuel increase particulate emissions. These results suggest that focusing on reducing fuel-derived EC in the production process of new cars would effectively reduce particulate emission from DISI cars. Highlights: Elemental carbon dominated the particulate mass. C20 –C28 hydrocarbons were dominant in both nano and accumulation-mode particles. Exhaust particles likely originated mainly from gasoline fuel. Less-volatile compounds in fuel seem to increase particulate emissions.